25th anniversary Rock & Roll Hall of Fame concerts [videorecording (DVD)]. - Gallen, Joel; Lewis, Jerry Lee; Raitt, Bonnie; Browne, Jackson; Taylor, James, 1948-; Wonder, Stevie; Robinson, Smokey, 1940-; Legend, John; King, B. B.; Sting (Musician); Beck, Jeff; Simon, Paul, 1941-; et al. (Time Life, 2010)
This videodisc features live and previously unseen performances, and includes the 2009 celebration of the Hall's silver anniversary, marked by two all-star New York Concerts that aired on HBO. Features U2 performing with Fergie and Mick Jagger, Bruce Springsteen with John Fogerty, Metallica, Aretha Franklin, and more.